(untitled) - Cantho University; Mekong Delta Community Biodiversity Development and Conservation (CanTho University, 1995)
The survey on Plant Genetic Resources for Major Crops in the rainfed saline zone of the Mekong Delta, Vietnam was undertaken in 1995 under Mekong Delta Community Biodiversity Development and Conservation (CBDC) Project. The survey was done to test these hypotheses: (1) Farmers have played an important role in plant genetic resource diversity, (2) Farmers have maintained and developed plant genetic resources diversity, and (3) Farmers' system is a good seed supply system
Keywords: Germplasm resources, plants; Vietnam